The suspensory ligamentous system of the penis: macro and micro anatomical examination of the adult male cadaveric specimen - Mariani, Ursula Meredith (My University, 2020)
Background: The suspensory ligamentous system of the penis lifts and supports the penis when erect, and plays a key role during coitus. The ligamentous system of the penis is a set of three ligaments that include the fundiform ligament, suspensory penile ligament (SPL) and the arcuate ligament. These ligaments are prone to injury during coitus and also play a key role in specific penile reconstruction procedures. The origin, course and insertion of each ligament remains a highly debated subject. In addition, their dimensions and histological composition are not clearly elucidated. The function of the penis is important, hence it is essential to examine and describe the macro and micro anatomy of the suspensory ligaments of the penis. Aim: The purpose of the current study was to investigate the macro and micro-anatomy of the suspensory ligamentous system of the penis in order to provide the knowledge base for successful penile reconstruction procedures that involve the suspensory ligamentous system of the penis. Materials and Methods: The study utilized a total of 49 cadavers from the dissection laboratories housed in the school of anatomical sciences at the University of the Witwatersrand. Three methods of analysis were employed including gross anatomy dissection to determine the origin, course and insertion of the suspensory ligaments, histological analysis to determine the cellular and fibre composition of each ligament and the MRI to elucidate the precise origin, course and insertion or each ligament complementing the gross anatomy dissection. Results: The fundiform ligament was found to have two sets of bundle fibres, a superficial and bilaterally placed arising from the Scarpa’s fascia and a deep and medially placed arising fromthe linea alba. Both ligaments split and encircled the penis and inserted into the superficial fascia of the penis. The SPL arose from the perichondrium of the pubic symphysis and inserted into the deep fascia (Buck’s fascia) of the penis. The arcuate ligament arose from the inferior aspect of the body of the pubis and pubic symphysis and inserted into the Buck’s fascia. The deep bundle of fibres of the fundiform ligament consists of more adipose tissue (43±2.02% ) and collagen fibres (43 ±1.6%) than both elastic (13±0.67 %) and reticular fibres (13 ±3.14 %). The superficial bundle of fibres of the fundiform ligament showed more adipose tissue (53±2.55%) and equal amounts of both collagen (21 ±1.79%) and elastic (23±0.35%) fibres but less reticular fibres (14±3.96%). Similarly, Page 5 the SPL consists of more adipose tissue (53±1.78%), equal amounts of collagen (23±1.35%) and elastic (23±0.82%) fibre and less reticular fibres (12±3.29%). Conclusion: The present study provided a depth of anatomical knowledge regarding the suspensory ligamentous system of the penis. Presenting clear information on the origin, course and insertion of each suspensory ligament and expounded on their histological composition. This information is valuable to anatomy subject and medical professionals particularly during interventional procedures around the penis and perineal region
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Anatomical Sciences, University of the Witwatersrand, Johannesburg, 2020